Fundamentals of electronic circuit design - Comer, David J (2003)
5 parts: Introduction to electronics; applycations of electronic circuits; amplifier models and frequency response; modeling and the operational amplifier; the mosffet; the Bjt; intergrated circuit design; integrated circuit design with the mossfet; integrated circuit design with the BJT